THE ROLE OF ORIGINAL REGIONAL INCOME AND BALANCE FUNDS IN EFFECTIVE CAPITAL SHOPPING TO INCREASE REGIONAL INDEPENDENCE IN CENTRAL PROVINCE - Mulyadi Mulyadi; Endah Nawangsasi (ProBank, 2019)
His study aims to analyze the role of Local Revenue, General Allocation Funds, Special Allocation Funds and SiLpa on Capital Expenditures in Districts/Cities in Central Java Province 2016-2017. The population in this study amounted to 35 districts/cities in Central Java. The sampling technique in this study used purposive sampling and obtained a sample of 33 districts/cities in Central Java. The data analysis technique used is multiple linear regression. The  results showed that the Regional Revenue and the Difference in Budget Financing have a positive and significant effect on capital expenditure, then the General Allocation Fund and the Special  Allocation Fund have a positive but not significant effect on capital  expenditure. The results of the determination test show that capital  expenditure is influenced by variables Independent of 79.5% and  the remaining 20.5% explained by variables outside this study. So the highest contribution is PAD in contributing to Capital Expenditures, because the contribution of the Balancing Fund, namely the General Allocation Fund and the Special Allocation Fund, is relatively small, meaning that the dependence on the Central Government is small,so the conclusion is that the higher the Regional Original Revenue, the greater the authority of the regional government in implement policies so that the region can be independent.